EFEKTIFITAS PENERAPAN ANCAMAN SANKSI PIDANA TAMBAHAN GUNA PENGEMBALIAN KERUGIAN KEUANGAN NEGARA DALAM TINDAK PIDANA KORUPSI (STUDI KASUS DI PENGADILAN NEGERI DENPASAR) - Kadek Krisna Sintia Dewi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
Research on the effectiveness and the application of criminal sanctions and punishment in addition to return financial losses caused by corruption ( case study at the Denpasar District Court ) aims to describe and analyze deeply, about the effectiveness of additional punishment, including the return of financial loss caused by corruption. In addition, this study also aims to determine and assess the constraints in the implementation of court decisions related to the return of financial loss. Based on this articles, the question that is whether the application of additional criminal sanction and punishment, including the return of state losses can be effective pursuant to the provisions of Article 18 of Law No. 31 Year of 1999 on Eradication of Corruption Jo . Law No. 20 year of 2001 on the Amendment of the Law No. 31 Year of 1999 on Eradication of Corruption. The method used in this research is the method of empirical juridical legal research of the descriptive research using primary and secondary data sources by document studying and interview techniques as well as articles related to the issues. Based on the research that has been done, it can be seen that the application of the additional sanction and punishment, including the return of state losses have applied but unfortunately have not been able to be effective in the aim of recovery effort of state losses due to corruption, and reduce the amount of corruption that occurred in the Denpasar District Court Jurisdiction . It is based on the data corruption cases in the year of 2012 increased from 20 cases to 25 cases in 2013. Returns of state losses in 2012 - 2013 amounted Rp.871.273.192 which is the corruption amount cases in the year of 2010 - 2011 . While the corruption cases in the year of 2012 – 2013, until recent time there are no recorded return of state losses. The constraints in the implementation of the court decisions related to the return of state losses, is convicted assets and property that has been transfered, multiple population administration, and duration of the judicial process to verdict and binding execution to be carried out .